Editorial to the Special Issue “Theranostic Drug Delivery: Prospects and Problems” - M. R. Mozafari (Biomedicines, 2024)
The technical phrase theragnostic (also known as theranostic) was first introduced to the scientific community in the year 1998 by John Funkhouser, to describe a methodology or procedure employed to achieve disease diagnosis and treatment simultaneously [...]